Nanotechnology in the Diagnosis and Treatment of Osteomyelitis - Demi Zapata; Jordan Higgs; Hunter Wittholt; Kishore Chittimalli; Amanda E. Brooks; Pranothi Mulinti (MDPI AG, 2022)
Infection remains one of the largest threats to global health. Among those infections that are especially troublesome, osteomyelitis, or inflammation of the bone, typically due to infection, is a particularly difficult condition to diagnose and treat. This difficulty stems not only from the biological complexities of opportunistic infections designed to avoid the onslaught of both the host immune system as well as exogenous antibiotics, but also from changes in the host vasculature and the heterogeneity of infectious presentations. While several groups have attempted to classify and stage osteomyelitis, controversy remains, often delaying diagnosis and treatment. Despite a host of preclinical treatment advances being incubated in academic and company research and development labs worldwide, clinical treatment strategies remain relatively stagnant, including surgical debridement and lengthy courses of intravenous antibiotics, both of which may compromise the overall health of the bone and the patient. This manuscript reviews the current methods for diagnosing and treating osteomyelitis and then contemplates the role that nanotechnology might play in the advancement of osteomyelitis treatment.